Host genotype and age shape the microbial community in the rhizosphere soils of Camellia forests - Lv, Jiayan; Huo, Chunyu; Zhang, Jianlang; Huang, Yongfang; Su, Yu; Lv, Yuzhou; Xie, Xianan; Chen, Zujing (Frontiers in Microbiology, 2024)
Microbiota living in the rhizosphere influences plant growth and fitness, from the opposite perspective, whether host genotypes control its root microbiota is of great interest to forest breeders and microbiologists. To improve low-yield plantations and promote sustainable management of Camellia oleifera, high-throughput sequencing was used to study the chemical properties and microbiome in rhizosphere soil of Camellia forests under three genotypes (common C. oleifera, local C. gauchowensis and C. chekiangoleosa) and three growth stages (sapling stage at four-year-old, primary fruit stage at seven-year-old and full fruiting stage at eleven-year-old). The results showed that the rhizosphere soil organic matter (OM), nutrient concentrations, diversity and community composition of the microbiome were significantly varied among different Camellia genotypes. The relative abundance of symbiotic and pathotrophic fungi in the rhizosphere soil of C. chekiangoleosa was significantly higher than that of C. gauchowensis. Concentrations of OM, available phosphorus (AP) and the bacterial alpha diversity increased with tree age. Fungi of Saitozyma, Mortierella and Glomeromycota, as well as bacteria of Burkholderia-Caballeronia-Paraccaberholderia and Vicinamibacterales had potential for fertilizer development for Camellia plantation. Camellia genotypes and growth stages were significantly correlated with the rhizosphere soil pH, OM and available potassium (AK). Soil pH and OM were key factors that affected the microbiome in the Camellia rhizosphere soils. In conclusion, tree genotypes and growth stages shaped microbial communities in Camellia rhizosphere soils, and some plant growth-promoting rhizobacteria were identified as preliminary candidates for improving Camellia plantations growth.